In vitro Drought Tolerant of Rootstock Apple (Malus domestica Borkh.) and Pear (Pyrus calleryana) - Danial, Gharbia H.; Ibrahim, Diaa A.; Khalil, Belan M.; Musa, Vyan M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The apple and pear explants were cultured in MS multiplication media supplemented with different concentrations of polyethylene glycol (6000), (0.0, 2%, 4%, and 6%). The results revealed that PEG at 6% was more effective than 2% and 4% by producing significantly lower average number of branches per explants (3.58) in apple and (3.62) in pear as compared to the highest average number of branches (6.06) in apple and (9.04) in pear achieved by control treatment. On the other hand, the shoot length and leaves number were reduced in both apple and pear at all PEG levels. After then, the plantlets were rooted in MS media supplemented with 1.0 mg/l NAA, and acclimatized in greenhouse. Under in vitro conditions callus induction from apple, the response of calli to elevated levels of PEG was recorded as fresh weight. These results indicated that increased levels of PEG were used to create water stress. There was a reduction in callus induction ability with increasing levels of PEG. And the control was superior compared to all other treatments.
Keywords: In vitro; Drought tolerant; Apple; Pear; Polyethylene glycol